The impact of chronic herpes virus infection on the bone system in children - M. A. Telesh; N. Yu. Krutikova; V. V. Sokolovskaya (LLC "Diagnostics and Vaccines", 2023)
Herpes virus infections currently are urgent problem in infectology, pediatrics and therapy. The feature of these diseases is the possibility of direct and indirect effects of the virus on various organs and systems: immune, nervous, endocrine, bone, in children in particular. The aim of the work is to summarize and systematize the available data on the impact of the chronic herpes virus infection on the bone system in children. Materials and methods: analysis of relevant Russian and international literature was carried out. Results: chronic herpes virus infections have pathological effects on bone system, in particular they can increase the risk of osteoporosis. Herpes viruses are involved in the pathogenesis of systemic inflammatory diseases, such as rheumatoid arthritis. Bone complications of herpes virus infections are the relevant issues. More research is needed to understand these complications more deeply.